Incident spectral solar irradiance measured above sea ice at station PS122/3_38-91 on 2020-05-02 - Marcel Nicolaus; Philipp Anhaus; Stefanie Arndt; Christian Katlein; Daniela Krampe; Benjamin Allen Lange; Ilkka Matero; Julia Regnery; Jan Rohde; Martin Schiller (PANGAEA, 2022)
Incident spectral solar irradiance measured above sea ice. The irradiance sensor (cos-collector) was installed on the sea ice for surface reference measurements (solar irradiance).
In: Nicolaus, M et al. (2021): Spectral solar radiation over and under sea ice during the MOSAiC campaign 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.935688